THE INFLUENCE OF ETNOSENTRISME OF ETHNIC STEREOTYPING AGAINST BALI TEEN ON TEEN ETHNIC CULTURAL BACKDROP IN LAMPUNG COMPOUND IN THE CITY OF BANDAR LAMPUNG - Retno Apriliani (Metakom, 2019)
The ethnic Balinese as ethnic newcomers coexist with the ethnic city of Bandar Lampung in Lampung and other ethnicities are very diverse, and there is a cultural concept assessment will be different. This research aims to know the extent of the influence of menganilisa and etniosentrisme on a Balinese against ethnic stereotyping of teenagers on teenage ethnic Lampung. In this study researchers using survey methods with types of quantitative research and supported by systems theory A-B-X Newcomb. This study uses variables X and Y, i.e. data obtained from the questionnaire to the spread of 98 respondents analyzed the data using simple regression. The results of this study demonstrate a significant influence among ethnic teen etnosentrisme on a Balinese against stereotype in teens of ethnic Cultural Backdrop in Lampung Compound in the city of Bandar Lampung with proceeds amounting to 5.5% and 94.5% the rest is influenced by other variables that are not part in this research. Key words: Compound Cultural , Etnosentrisme, and Stereotyping.